Control of intake boundary conditions for enabling clean combustion in variable engine conditions under intelligent charge compression ignition (ICCI) mode. (15th September 2020) - Li, Zilong; Zhang, Yaoyuan; Huang, Guan; Zhao, Wenbin; He, Zhuoyao; Qian, Yong; Lu, Xingcai
Highlights: Intake condition effects on dual-fuel ICCI mode were studied in a wide load range. Applicable intake pressure for wide-range ICCI operation were advised. Combining EGR and gasoline multi-injection reached low emissions at medium load. Enhancing intake temperature was an effective way to operate ICCI at low loads. Abstract: In a brand-new dual-fuel combustion mode called intelligent charge compression ignition (ICCI), the intake boundary conditions, including intake pressure, exhaust gas recirculation rate, and intake temperature, were modulated towards high-efficiency and clean combustion. A series of experiments were conducted in a modified single-cylinder engine. Commercial gasoline and diesel were respectively supplied to two decoupled common-rail direct injection systems. The experimental results show that intake pressure has a significant influence on ICCI combustion and emissions. The applicable intake pressure and gasoline ratio for ICCI steady operation under different engine loads are advised in this paper. At medium to high loads, exhaust gas recirculation is used to maintain stable combustion and delay combustion phasing. At 8 bar indicated mean effective pressure, slight exhaust gas recirculation (about 20% in this paper) could ease the combustion rate and adjust combustion phasing, optimizing heat release profiles. Gasoline double injection can further decrease hydrocarbon and carbon monoxide emissions but increase particulate matter emissions, maintaining nitrogen oxide emissions near EURO VI standard. At low engine load, the intake temperature is enhanced to make up low in-cylinder reactivity. The cooperation control of fuel supply ratio, diesel injection timing, and intake temperature is conducted to increase combustion efficiency and decrease nitrogen oxide and particulate matter emissions.